On the validity of the publication of two Linnaean names, Rubus creticus and R. maximus (Rosaceae) - Ferrer-Gallego, P. Pablo; de Beek, Abraham Van (Phytotaxa, 2025)
Recently, discussions arose about the validity of the publication of two names that were published by Linnaeus: Rubus creticus Linnaeus (1756: 15) and R. maximus Linnaeus ex Loefling (1758: 7) (Rubeae Dumortier (1829: 39), Rosaceae Jussieu (1789: 334)). Because the status of these names effects the correct names of Rubus taxa, clarity about these is due. Nomenclature articles cited throughout the text follow the International Code of Nomenclature for algae, fungi, and plants (Turland et al. 2018).